Comparative efficacy and safety of antipseudomonal β-lactams for pediatric febrile neutropenia: A systematic review and Bayesian network meta-analysis. Issue 50 (17th December 2021) - Tan, Xinmei; Li, Yan; Xi, Jiaxi; Guo, Sitong; Su, Henghai; Chen, Xiaoyu; Liang, Xueyan
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Antipseudomonal β-lactams have been used for the treatment of febrile neutropenia (FN); however, the efficacy and safety of antipseudomonal β-lactams in pediatric patients remain unclear. The aim of this study was to comprehensively compare the efficacy and side effects of optional antipseudomonal β-lactams for pediatric FN. Methods: PubMed, Embase, Medline, and Cochrane Library were systematically searched from their inception to December 18, 2020. Eligible randomized controlled trials in which pediatric FN patients were treated with an empiric monotherapy of antipseudomonal β-lactams were selected. Data synthesis was performed using WinBUGS 14.0 software and meta packages implemented in R 3.6.2. Random-effects network meta-analysis was performed, and dichotomous data were pooled as odds ratios with 95% confidence intervals. The primary outcome was treatment success without modification; the secondary outcomes were adverse events (AEs), all-cause mortality, and new infections. The GRADE tool was used to assess the quality of the evidence. The protocol was registered with PROSPERO ID CRD42021226763. Results: Eighteen studies with 2517 patients were included. The results showed no statistically significant difference between the optional antipseudomonal β-lactams in the outcomes of treatment success without modification, all AEs, all-cause mortality, and new infections for pediatric FN. Based on the results of Bayesian rank probability, meropenem was ranked highest among all the treatment options with regard to treatment success without modification benefit; ceftazidime and meropenem were associated with a lower risk of AEs; cefoperazone/sulbactam and piperacillin/tazobactam were associated with a lower risk of mortality, and piperacillin/tazobactam and meropenem were associated with a lower risk of new infections. The quality of evidence was moderate. Conclusions: Meropenem and piperacillin/tazobactam were found to be better with regard to treatment success without modification, with a comparable safety profile. Therefore, our findings support the use of meropenem and piperacillin/tazobactam as a treatment option for pediatric FN patients.